2022
DOI: 10.1111/jfpp.17017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pretreatment methods on total ascorbic acid, total phenolic content, and color of soursop ( Annona muricata L.) Pulp. Steam blanching, hot water blanching, and microwave‐assisted blanching

Abstract: Soursop fruits comprise many bioactive compounds that potentially support human health. The processing method dramatically affects the antioxidant activity found in the soursop fruit. This study aimed to explore the effects of preheating treatment approaches (steam blanching, hot water blanching, and microwave‐assisted blanching) on the physiochemical properties of soursop fruit. The changes in colors, total ascorbic acid, and total phenolic content were based on the variations in surveyed parameters including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
2
4
0
Order By: Relevance
“…This results in increased polarity of the molecules, generating higher temperatures caused by increases in vibration and friction of the molecules [15,29]. The present results agree with [27] and [30] research, who present an inverse relation between the power level and residual enzymatic activity of the peroxidase when microwaves were applied to lettuce (Lactuca sativa), broccoli (cv.…”
Section: Peroxidase Enzyme Inactivation In Tamarillosupporting
confidence: 91%
See 3 more Smart Citations
“…This results in increased polarity of the molecules, generating higher temperatures caused by increases in vibration and friction of the molecules [15,29]. The present results agree with [27] and [30] research, who present an inverse relation between the power level and residual enzymatic activity of the peroxidase when microwaves were applied to lettuce (Lactuca sativa), broccoli (cv.…”
Section: Peroxidase Enzyme Inactivation In Tamarillosupporting
confidence: 91%
“…The retention of total phenolics during microwave, this result may be due to the fact that the energy provided in blanching by microwaves and water can cause a rupture of the cell walls, facilitating the release of phenolics linked to pectin, cellulose, hemicellulose and traces of lignin from the cell wall, which can cause a higher extraction rate compared to the degradation of phenols in the fruit [21]. On the other hand, by inhibiting the peroxidase enzyme it was possible to prevent the oxidation of monophenolic compounds from being catalyzed to o-diphenol and o-dihydroxy to o-quinones [15]. These ndings are consistent with the results of previous research conducted by [14] and [15], which found that in comparison with untreated samples of gooseberry (Phyllanthus emblica) and soursop (Annona muricata L.), the total phenol content for the rst case increased (6%) and for the second they were maintained after blanching with microwave.…”
Section: Effect Of Microwave Blanching On Bioactive Compounds and Col...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the color difference values have shown that heat pump drying has a possible result in giving a bright yellow color to mango pulp; however, some bioactive compounds are not retained much at low concentrations.Specifically,theTPCvaluefrom188.99 ± 8.42 mg/gDW was reduced to 12 ± 0.04 mg/g DW (50°C), giving the TAA value (from 0.64 mg/g DW) remaining 0.08 ± 0.02 mg/g DW, total flavonoid content (TFC) remaining 0.82 mg/g DW; DPPH remaining 1.58 ± 0.08 mg/g DW compared to the original 29.82 ± 0.04 mg/g DW. This may be due to the low drying temperature and continuous drying for a long time, leading to long exposure to heat and environment, so the bioactive compounds are decomposed (Nhi et al, 2022;Ortiz et al, 2013).…”
Section: Effect Of Foam Mat Drying On the Quality Of Mango Pulpmentioning
confidence: 99%